Knowledge of parents regarding newborn screening test, after accessing the website “Babies’ Portal” - Heel prick test - Mendes,Caroline Antonelli (2017)
ABSTRACT Purpose: to assess the knowledge of mothers about the heel prick test, develop contents on this test to make it available on the "Babies’ Portal" website, evaluate and validate the informative material developed. Methods: this study was conducted in three stages, that is, the first stage which is about a descriptive study involving 105 mothers of newborn children before performing the neonatal screening "Heel Prick Test", the second one consisting in the development of the website "Babies’ Portal", and the third stage, the evaluation and validation of this material carried out by 20 parents of children between zero and 36 months old, who underwent the neonatal screening Heel Prick Test by accessing the website “Babies’ Portal”. Results: although the interviewed mothers knew that their children had the right to be tested, they showed no knowledge of the diseases that can be prevented, time of diagnosis, nor the consequences arising from the lack of early diagnosis and treatment. The website creation and validation gathered basic information about the Heel Prick Test, and the participants regarded the content from satisfactory to excellent. Conclusion: it is necessary that families know not only about the procedures their children will undergo, but also the reason they are performed and the consequences of failing in doing so.